The Necessity of/and Challenges to International Project Financing of Hydropower Projects in Nepal - Neupane, Anjan (Hydro Nepal: Journal of Water, Energy and Environment, 2014)
Although development of 40,000 MWs of hydropower plants in Nepal is said to be feasible from an engineering/economic perspective, from a financing through Nepalese banks perspective, it is impossible. Loans from international banks are needed to finance hydropower projects in Nepal as local banks do not have capacity to support large projects. However, most international banks have not yet been interested as many Nepalese projects are not yet considered “bankable” from a project finance perspective. There are many challenges to financing hydropower projects as the financing requires the project itself to be free of risk from a legal and contractual viewpoint, thus making it worthy of being used as collateral on its own right. The only way forward is for the government to change its policies significantly to ensure the bankability of projects currently being developed by many independent power producers. DOI: http://dx.doi.org/10.3126/hn.v13i0.10033 HYDRO NEPAL Journal of Water, Energy and Environment Issue No. 13, July 2013 Page: Uploaded date: 3/12/2014